2016
DOI: 10.1175/bams-d-14-00194.1
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Foehn Warming in the Lee of Mountains

Abstract: The foehn effect is well known as the warming, drying, and cloud clearance experienced on the lee side of mountain ranges during “flow over” conditions. Foehn flows were first described more than a century ago when two mechanisms for this warming effect were postulated: an isentropic drawdown mechanism, where potentially warmer air from aloft is brought down adiabatically, and a latent heating and precipitation mechanism, where air cools less on ascent—owing to condensation and latent heat release—than on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 27 publications
8
142
2
Order By: Relevance
“…Since föhn flow is synoptically driven, the results have shown that föhn events are linked to the large-scale Southern Hemisphere circulation pattern. There is evidence that both the thermodynamic and the dynamic mechanism are responsible for föhn warming on South Georgia, and this is similar to the conclusions of Elvidge et al (2014a) and Elvidge & Renfrew (2015) who looked at föhn dynamics over the Antarctic Peninsula. We now know that the asymmetry of the South Georgia's regional climate is a result of the interaction between the island's topography and the 321 prevailing westerly winds, resulting in the föhn warming process.…”
Section: Synthesissupporting
confidence: 77%
See 1 more Smart Citation
“…Since föhn flow is synoptically driven, the results have shown that föhn events are linked to the large-scale Southern Hemisphere circulation pattern. There is evidence that both the thermodynamic and the dynamic mechanism are responsible for föhn warming on South Georgia, and this is similar to the conclusions of Elvidge et al (2014a) and Elvidge & Renfrew (2015) who looked at föhn dynamics over the Antarctic Peninsula. We now know that the asymmetry of the South Georgia's regional climate is a result of the interaction between the island's topography and the 321 prevailing westerly winds, resulting in the föhn warming process.…”
Section: Synthesissupporting
confidence: 77%
“…Turbulent sensible heating caused by leeside mixing may also produce warm, dry winds as the flow passes over a mountain range (e.g. Scorer, 1978;Elvidge et al, 2014b;Elvidge & Renfrew, 2015). Regardless of the mechanism responsible for their warmth and dryness, the driving force behind a föhn wind is either through cross-mountain synoptic flow or by cross-mountain pressure gradient flow.…”
Section: The Dynamical Mechanismmentioning
confidence: 99%
“…Furthermore, shear-driven turbulence in the first hundred meters above the surface (not shown) may have mixed down potentially warmer air from aloft and aid in warming of the lee slopes. Adiabatic warming due to subsidence on lee slopes has been widely documented and is associated with downslope Foehn-like winds (Gaffin 2002(Gaffin , 2009Richner and Hächler 2013) and several mechanisms have been proposed to explain the formation of these winds (Elvidge and Renfrew 2016), including mountain waves (Blier 1998;Zängl et al 2004) as identified in the present study. Accordingly, the formation of warm winds on NM would follow the model that Elvidge and Renfrew (2016) termed ''isentropic drawdown''.…”
Section: Numerical Simulationsmentioning
confidence: 50%
“…Thus, these data provide compelling evidence that understanding the frequency with which higher elevations are exposed to different layers of the atmosphere may be critical for evaluating their sensitivity to changing climatic conditions. probable contributors to this weak föehn flow [29]. This drawdown competed with thermally forced anabatic winds to modulate temperature and humidity at higher elevations on the mountain, until the convective PBL finally enveloped the summit during the early afternoon (Figure 9c…”
Section: Discussionmentioning
confidence: 99%
“…These finding suggest that the~4-8 m s −1 wind at the summit (Figure 8) was sufficient to cause weak föehn flow [10,15] associated with periodic downward mixing of drier EZ air on the lee side of the mountain. Given that the drier air was observed at higher elevations during the time that the convective PBL was growing and orographic clouds had mostly dissipated, isentropic drawdown and/or mechanical mixing are probable contributors to this weak föehn flow [29]. This drawdown competed with thermally forced anabatic winds to modulate temperature and humidity at higher elevations on the mountain, until the convective PBL finally enveloped the summit during the early afternoon (Figure 9c).…”
Section: Discussionmentioning
confidence: 99%